Pengembangan Media Pembelajaran Bangun Ruang Berbasis Augmented Reality - Baiq Desi Dwi Arianti; Muhammad Djamaluddin; Hani Sabila (Fakultas Teknik Universitas Hamzanwadi, 2023)
The implementation of the Merdeka Curriculum (MC) is a program launched by the Indonesian government to enhance the quality of education at all levels. Despite the MC providing flexibility and facilitation for deep learning focused on character development, the utilization of Augmented Reality (AR) in education remains limited in Indonesian schools. Therefore, this research aims to address the research gap and offer research novelty by developing an innovative AR-based spatial geometry instructional media. This study adopts the ADDIE (Analysis, Design, Development, Implementation, Evaluation) methodological approach and involves four experts, including two media experts and two subject matter experts, for the feasibility assessment. Additionally, 25 fifth-grade students from SDN 2 Sandubaya serve as respondents in this research. The findings reveal that the developed instructional media has received high feasibility ratings from media experts (87%) and subject matter experts (84%). Moreover, users' responses towards the application yielded a positive rating of 99%. Thus, this research makes a significant contribution to the field of AR-based instructional media development by addressing the research gap concerning the utilization of AR in spatial geometry education within Indonesian schools. Furthermore, this study offers novelty by introducing an innovative approach to instructional media development, garnering positive user outcomes. The developed instructional media can serve as an effective and engaging resource for spatial geometry education for fifth-grade students